Assessing and improving your teaching : strategies and rubrics for faculty growth and student learning - Blumberg, Phyllis, 1933- (Jossey-Bass higher and adult education series., 2013)
"Don't wait for someone else to tell you what you need to do to make your teaching more effective--figure it out for yourself and invigorate your teaching on your own terms. This practical evidence-based guide promotes excellence in teaching and improved student learning through self-reflection and self-assessment of one's teaching. Phyllis Blumberg starts by reviewing the current approaches to instructor evaluation and describes their inadequacies. She then presents a new model of assessing teaching that builds upon a broader base of evidence and sources of support. This new model leads to self-assessment rubrics, which are available for download, and the book will guide you in how to use them. The book includes case studies of completed critical reflection rubrics from a variety of disciplines, including the performing and visual arts and the hard sciences, to show how they can be used in different ways and how to explore the richness of the data you'll uncover"--